2013
DOI: 10.1111/jdv.12086
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus abrogates TGF‐β1‐induced type I collagen production in normal human fibroblasts through suppressing p38MAPK signalling pathway: implications on treatment of chronic atopic dermatitis lesions

Abstract: The present results demonstrated that tacrolimus significantly inhibited physiological functions of fibroblasts enhanced by TGF-β1 in vitro. Clinically, we propose that topical tacrolimus may not only reduce AD recurrence but also ameliorate dermal fibrosis often seen in chronic AD lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
(124 reference statements)
0
20
0
Order By: Relevance
“…Interestingly, immunosuppressive peptidyl-prolyl isomerase inhibitors like FK506 have been ascribed potent antifibrotic effects in lung fibrosis (40)(41)(42)(43). FK506 suppresses collagen synthesis and expression of the TGF-b 1 receptor in dermal and lung fibroblasts, but the underlying mechanisms are largely unclear (41,44,45). Our findings put forward the possibility that inhibition of FKBP10 might contribute to the antifibrotic effects of FK506.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, immunosuppressive peptidyl-prolyl isomerase inhibitors like FK506 have been ascribed potent antifibrotic effects in lung fibrosis (40)(41)(42)(43). FK506 suppresses collagen synthesis and expression of the TGF-b 1 receptor in dermal and lung fibroblasts, but the underlying mechanisms are largely unclear (41,44,45). Our findings put forward the possibility that inhibition of FKBP10 might contribute to the antifibrotic effects of FK506.…”
Section: Discussionmentioning
confidence: 78%
“…Fibroblasts are the most common producers of collagen and are subject to complex autocrine and paracrine cytokine signals to regulate its formation, of which TGFβ is crucial [66, 67]. In combination with these cytokines there are a number of enzymes and proteins that through cleavage or binding can affect collagen turnover [68].…”
Section: Resultsmentioning
confidence: 99%
“…In AD, repeated scratching turns the erythematous acute lesions into lichenified chronic and intractable ones . The lichenified and thickened skin lesions are a result of epidermal acanthosis and dermal fibrosis . Lan et al demonstrated that tacrolimus significantly downregulated the proliferation of human fibroblasts and their production of collagen I, both of which were stimulated by transforming growth factor β‐1.…”
Section: Suppression Of Allergic Inflammation By Tacrolimusmentioning
confidence: 99%
“…The lichenified and thickened skin lesions are a result of epidermal acanthosis and dermal fibrosis . Lan et al demonstrated that tacrolimus significantly downregulated the proliferation of human fibroblasts and their production of collagen I, both of which were stimulated by transforming growth factor β‐1. Caproni et al quantified the profile of inflammatory cell infiltration in the lesional skin before and after treatment with topical tacrolimus and topical hydrocortisone butyrate.…”
Section: Suppression Of Allergic Inflammation By Tacrolimusmentioning
confidence: 99%